Sistema de conservación para la mora Castilla en el departamento de Antioquia - Bohórquez Villamizar, Andrés Sebastián (Arquitectura, Arte y Diseño, 2017)
In the economy of the country are several sectors that have contributed to national and international development from the resources with which our territory has; The agricultural sector is one of the economic potential of the country, for many years thousands of hectares have been cultivated around the great variety of fresh produce. The blackberry is one of the most perishable fruits, its deterioration is due to external factors such as climate change, transportation, handling and political situations affecting the country's roads, in addition to its organoleptic characteristics such as taste, appearance, texture And their physiological phenomena of respiration and perspiration; This project sought to provide a solution by developing a system that improves the conservation of blackberry from the time of harvest until its arrival at the point of commercialization to reduce losses of this product. This project is an exploratory one, it investigated alternatives of conservation for the blackberry during its chain of supply in the department of Antioquia, involving the three main phases the culture, the transport and the commercialization; It also seeks to include the different users of the chain such as growers, transporters and merchants.